From Separate Silos to a Cohesive Whole: The story of Integrated Medical Education - Komal Atta (Aziz Fatimah Medical and Dental College, 2023)
An integrated curriculum broadly refers to collaborative methodologies of studying various disciplines together in a linked form. This has widely become the method of choice for imparting undergraduate medical education.1 In the context of Pakistan, where the medical education is predominantly based on a traditional discipline based approach, the examples of implemented integrated curricula have been few and far between due to a number of factors namely, logistics, faculty training, faculty readiness, student to teacher ratio and infra structure being a few prominent ones. 2 Despite these challenges, the University of Health Sciences (UHS) recently took up the task to introduce an integrated medical curriculum in Pakistan, the curriculum "2k23" has now been implemented in the 50 constituent colleges of the UHS.